2021
DOI: 10.1111/jfbc.13992
|View full text |Cite
|
Sign up to set email alerts
|

Niazimicin: A thiocarbamate glycoside from Moringa oleifera Lam. seeds with a novel neuroprotective activity

Abstract: Moringa oleifera (MO) known as the miracle tree is a famous nutritional source in many countries. In this study, the neuroprotective activity of MO seeds was investigated. Fractions of the 70% ethanol seed extract of MO were injected at a dose of 250 mg kg−1 day−1 to albino rats for 15 days, after‐which induction of dementia was done using 100 mg/kg AlCl3 over 30 days. Results revealed that all fractions ameliorated the effects of AlCl3 where methylene chloride and ethyl acetate fractions, containing the major… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 43 publications
1
11
0
Order By: Relevance
“…Our results revealed an increased Aβ load in the APP/PS1 mice that was tremendously alleviated by the MO treatment as indicated by the western blot, thioflavin S, and ELISA experiments. This is consistent with our previous study [ 21 ] and a recent study that showed that the component of MO Niazimicin decreases Aβ in albino rate [ 27 ], confirming the ability of MO to reduce Aβ burden.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results revealed an increased Aβ load in the APP/PS1 mice that was tremendously alleviated by the MO treatment as indicated by the western blot, thioflavin S, and ELISA experiments. This is consistent with our previous study [ 21 ] and a recent study that showed that the component of MO Niazimicin decreases Aβ in albino rate [ 27 ], confirming the ability of MO to reduce Aβ burden.…”
Section: Discussionsupporting
confidence: 93%
“…However, many of the Aβ-targeted therapies have failed [ 17 , 18 , 19 , 20 ]. This failure and the multifactorial complexity of AD trigger therapeutic interest in products with multiple effects such as nutraceuticals such as Moringa oleifera (MO), Tamarix gallica, Ginkgo biloba , Codonopsis pilosula polysaccharide, and Ferulic acid, which have shown potential antioxidative, anti-inflammatory, and neuroprotective virtues among others [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quercetin and kaempferol derivatives are the main polyphenols in Moringa oleifera leaves. Many studies have reported that these two kinds of compounds have neuroprotective effects [89,90]. What is worth considering is whether these two kinds of compounds play a major role in the neuroprotective effect of polyphenols in Moringa oleifera leaves.…”
Section: Effect Of Polyphenols In Mlpe Against H 2 O 2 -Induced Oxidative Stress In Pc-12 Neuroblastoma Cellsmentioning
confidence: 99%
“…The influx of neutrophils, monocytes, and lymphocytes, as inflammatory cells, to the stimulation' site is a fundamental component of inflammation. The activated inflammatory cells at the site of inflammation release chemical mediators such as chemokines, cytokines, eicosanoids and nitric oxide causing elevation in superoxide, hydroxyl radical, hydrogen peroxide and tissue damage [6,9,10]. Thus, the over expression of the proinflammatory genes activates an intracellular signaling cascade generating additional ROS which in turn increase the oxidative stress and inflammatory lesion which drive the progression of liver disorders [6].…”
Section: Introductionmentioning
confidence: 99%